2021
DOI: 10.1111/1467-9566.13362
|View full text |Cite
|
Sign up to set email alerts
|

Sociological contributions to race and health: Diversifying the ontological and methodological agenda

Abstract: Sociologists have made fundamental contributions to the study of race and health in the United States. They have disrupted biological assumptions of race, uncovered individual and structural factors that drive racial health disparities and explored the effects of racism on health. In recent years, however, with broader shifts towards big data, the work to understand the dynamics between race and health has been increasingly pursued from a quantitative perspective. Often, such analyses isolate intermediary mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 124 publications
0
2
0
Order By: Relevance
“…As highlighted by Nelson and Spencer (2021), current sociological conceptualizations of race, maternal health, and well‐being have been limited to birth weight measures or self‐reported health. Examining the well‐being of Black mothers qualitatively allowed for further interrogation into the racialized pathways that are connected to their perceived well‐being.…”
Section: Current Studymentioning
confidence: 99%
“…As highlighted by Nelson and Spencer (2021), current sociological conceptualizations of race, maternal health, and well‐being have been limited to birth weight measures or self‐reported health. Examining the well‐being of Black mothers qualitatively allowed for further interrogation into the racialized pathways that are connected to their perceived well‐being.…”
Section: Current Studymentioning
confidence: 99%
“…58 Interview participants were 93% White; scholars have shown that end-of-life experiences and perceptions vary by race. 80 Eighty-six percent of the sample was also over 40 years of age.…”
Section: Limitationsmentioning
confidence: 99%